Fatty Acid Alpha-oxidation and its Clinical Correlation (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
The human diet includes branched chain fatty acid phytanic acid (3,7,11,15-tetramethylhexadecanoic acid) and the degradation  of 2-hydroxyphytanoyl-CoA, the initial step in the oxidation of phytanic acid was investigated.  But, the long-standing controversy about the mechanism and subcellular location of phytanic acid alpha-oxidation has been debated and remain incompletely understood. Phytanic acid is known to undergo one cycle of alpha-oxidation initially due to its methyl group at the beta-position. The metabolic pathway known as Alpha oxidation of fatty acid is important for the production of energy, the elimination of toxic metabolites, the metabolism of lipids, the regulation of fatty acid levels, and developmental processes. The resulting pristanic acid can undergo further oxidation through a peroxisomal process called beta oxidation. Throughout the years, even more diseases including the accumulation of phytanic acid along with other metabolites were documented. Numerous hereditary disorders that affect mitochondrial fatty acid beta-oxidation, peroxisomal fatty acid beta-oxidation, or mitochondrial fatty acid alpha-oxidation have been found in humans. Defective alpha-oxidation in peroxisome biogenesis disorders causes phytanic acid levels to accumulate, resulting in Refsum disease, a rare autosomal recessive disorder. Only a few, unfavorable alternatives to treatment are available. The prognosis for Refsum disease is still not promising. Consequently, this brief review is to summarize the biochemistry of alpha fatty acid oxidation, the effects of the biochemical defect and its associated disease, and the clinical hallmarks of Refsum disease, which have been associated to the degradation of exogenous 3-methyl-branched fatty acid.